I can see in the dark - Fossum, Karin, 1954- (Houghton Mifflin Harcourt, 2014)
"Riktor doesn't like the way the policeman storms into his home without even knocking. He doesn't like the arrogant way he walks around the house, taking note of its contents. The policeman doesn't bother to explain why he's there, and Riktor is too afraid to ask. He knows he's guilty of a terrible crime and he's sure the policeman has found him out. But when the policeman finally does confront him, Riktor freezes. The man is arresting him for something totally unexpected. Riktor doesn't have a clear conscience, but the crime he's being accused of is one he certainly didn't commit. Can he clear his name without further incriminating himself?" --